Old divergence and restricted gene flow between torrent duck ( Merganetta armata ) subspecies in the Central and Southern Andes - Alza, Luis (2019)
Aim: To investigate the structure and rate of gene flow among populations of habitat‐specialized species to understand the ecological and evolutionary processes underpinning their population dynamics and historical demography, including speciation and extinction.Location: Peruvian and Argentine Andes.Taxon: Two subspecies of torrent duck (Merganetta armata).Methods: We sampled 156 individuals in Peru (M. a. leucogenis; Chillón River, n = 57 and Pachachaca River, n = 49) and Argentina (M. a. armata; Arroyo Grande River, n = 33 and Malargüe River, n = 17), and sequenced the mitochondrial DNA (mtDNA) control region to conduct coarse and fine‐scale demographic analyses of population structure. Additionally, to test for differences between subspecies, and across genetic markers with distinct inheritance patterns, a subset of individuals (Peru, n = 10 and Argentina, n = 9) was subjected to partial genome resequencing, obtaining 4,027 autosomal and 189 Z‐linked double‐digest restriction‐associated DNA sequences.Results: Haplotype and nucleotide diversities were higher in Peru than Argentinaacross all markers. Peruvian and Argentine subspecies showed concordant species‐level differences (ΦST mtDNA= 0.82;ΦST autosomal = 0.30;ΦST Z chromosome = 0.45),including no shared mtDNA haplotypes. Demographic parameters estimated formtDNA using IM and IMa2 analyses, and for autosomal markers using ∂a∂i (isolation‐with‐migration model), supported an old divergence (mtDNA = 600,000 years before present (ybp), 95% HPD range = 1.2 Mya to 200,000 ybp; and autosomal ∂a∂i = 782,490 ybp), between the two subspecies, characteristic of deeply divergedlineages. The populations were well‐differentiated in Argentina but moderately differentiated in Peru, with low unidirectional gene flow in each country.Main conclusions: We suggest that the South American Arid Diagonal was preexisting and remains a current phylogeographic barrier between the ranges of the two torrent duck subspecies, and the adult territoriality and breeding site fidelity to the rivers define their population structure.